1998
DOI: 10.1093/bja/81.6.925
|View full text |Cite
|
Sign up to set email alerts
|

Opioid receptor independent effects of morphine on membrane currents in single cardiac myocytes

Abstract: We have examined the effects of morphine, a mu-opioid receptor agonist, on various membrane ionic currents in rat ventricular and human atrial myocytes, using patch-clamp techniques in the whole-cell configuration. Morphine produced a concentration-dependent reduction in peak transient sodium current. When the sodium current (INa) was evoked at 5-s intervals the estimated IC50 for morphine was approximately 30 mumol litre-1. Morphine 10 mumol litre-1 inhibited INa with a 5-mV shift in the potential-dependent i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…51 Morphine also hyperpolarizes the cardiac resting membrane potential by increasing the inwardly rectifying K + current (I KI ), an action apparently not mediated by opioid receptors. 52,53 Morphine and other opioids induce pharmacologic preconditioning of the myocardium. [54][55][56] The underlying mechanism involves K ATP channels, as with the inhalational anesthetics.…”
Section: Opioidsmentioning
confidence: 99%
“…51 Morphine also hyperpolarizes the cardiac resting membrane potential by increasing the inwardly rectifying K + current (I KI ), an action apparently not mediated by opioid receptors. 52,53 Morphine and other opioids induce pharmacologic preconditioning of the myocardium. [54][55][56] The underlying mechanism involves K ATP channels, as with the inhalational anesthetics.…”
Section: Opioidsmentioning
confidence: 99%
“…In rabbit ventricular myocytes, morphine significantly increased I K1 , independent of the opioid-receptor pathway [42]. In human atrial myocytes, morphine was unable to enlarge I K1 [63].…”
Section: Morphinementioning
confidence: 88%
“…Moreover, it has been shown that the cardiac effects of opioids could be or not be dependent on opioid receptors. The effects of morphine on ionic currents in cardiac myocytes have shown not to depend on opioid receptor 24 or to be mediated via d-and k-receptors 25 . However, its cardioprotective effect is known to be due to the activation of d-receptors 26,27 .…”
Section: Discussionmentioning
confidence: 99%